2017
DOI: 10.1007/s00268-017-4066-8
|View full text |Cite
|
Sign up to set email alerts
|

Biological Implant for Complex Abdominal Wall Reconstruction: A Single Institution Experience and Review of Literature

Abstract: Biological materials have the potential to reduce morbidity and improve outcome of definitive repair of CAWR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…A literature review on biological meshes found that Permacol is one of the most studied mesh types in the published literature 28 , especially in the context of CAWD repair. These studies, however, are mainly retrospective, single institution case series 5,9,[12][13][14][28][29][30][31][32][33][34] with only three multicenter retrospective studies 3,15,22 and one cross-sectional study 21 published to date. Our series of 60 patients represents the first large, multi-centre Italian study on Permacol mesh implants in patients with CAWD.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A literature review on biological meshes found that Permacol is one of the most studied mesh types in the published literature 28 , especially in the context of CAWD repair. These studies, however, are mainly retrospective, single institution case series 5,9,[12][13][14][28][29][30][31][32][33][34] with only three multicenter retrospective studies 3,15,22 and one cross-sectional study 21 published to date. Our series of 60 patients represents the first large, multi-centre Italian study on Permacol mesh implants in patients with CAWD.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 93.3% of the patients were modified VHWG grade 2-3, reflecting the high rate of comorbidities and CAWDs with a contaminated surgical field. In patients with VHWG grade 1 (6.7%), a biological mesh was www.nature.com/scientificreports www.nature.com/scientificreports/ indicated due to the presence of a defect >10 cm, multiple previous repair attempts or multiple defects, as indicated by CAWD characteristics 5 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations